Secreted Frizzled Related Protein 4: A Novel Marker of Pancreatic Beta Cell Dysfunction In Prediabetic Obese Subjects - Mukesh, Kumar; Neelima, Singh; Kumar, Sharma Ashish (Indian journal of clinical biochemistry, 2022)
INTRODUCTION: Secreted frizzled-related protein 4 (SFRP4) is a proinflammatory cytokine and a potent regulator of Wnt/[beta] catenin signaling pathway. It causes apoptosis of [beta] cells and decreases expression of [Ca2.sup.+] channels thereby its concentration is increased in the obesity and impaired glucose tolerance. AIMS AND OBJECTIVES: The objective of the present study was to investigate whether the SFRP4 concentration in serum is altered in obesity and impaired glucose tolerance. MATERIALS AND METHODS: The present study includes 30 prediabetic obese subjects (IGT group) and 30 normal healthy individuals as controls. In all the cases and controls, Oral glucose tolerance tests were conducted and Serum SFRP4 levels were measured by ELISA. RESULTS AND CONCLUSION: Levels of serum SFRP4 in the IGT group (cases) were significantly higher than those in the Control group (P < 0.001). The serum SFRP4 levels were positively correlated with BMI, IGT and HOMA-IR and were negatively correlated with HDL-C. Our study provides evidence that the concentrations of serum SFRP4 in prediabetic obese subjects were increased and correlated closely with pancreatic beta cell dysfunction and obesity (chronic low-grade inflammation). Hence, SFRP4 may participate in the development of pancreatic beta cell dysfunction in prediabetic obese subjects. KEYWORDS: SFRP4, prediabetes, obesity, Wnt signaling, IGT, HOMA-IR